The role of DLL4-NOTCH signalling in endothelial cell metabolism - Harjes, U (2014)
Tumour tissue is characterised by fluctuating oxygen concentrations, decreased nutrient supply, and acidic pH. Angiogenic signalling pathways that drive a certain metabolic 'configuration' may give endothelial cells a selective advantage in the tumour environment. Previously it has been shown that glycolysis drives proliferation, migration and tip cell formation during sprouting of endothelial cells (De Bock, Georgiadou et al. 2013), and is increased by VEGFA. DLL4-NOTCH has been shown to limit angiogenesis and slow down proliferation of endothelial cells, and promote stalk cell formation during angiogenic sprouting, leading to sprout elongation. DLL4-NOTCH is implicated in tumour angiogenesis, and its overexpression is a potential mechanism of resistance to anti-VEGFA therapy (Li, Sainson et al. 2011). This thesis aimed at investigating the effect of the DLL4-NOTCH signalling pathway on endothelial metabolism and its implications in angiogenesis. Firstly, it was found that DLL4-NOTCH decreases the glycolytic rate and mitochondrial respiratory parameters in endothelial cells. When given exogenous fatty acids, DLL4-NOTCH activation caused increased fatty acid uptake, storage and oxidation. This shows that the induction of DLL4-NOTCH signalling results in increased fatty acid utilisation. Secondly, this research identified fatty acid oxidation as a target metabolism pathway for angiogenic therapy. More specifically, inhibition of fatty acid oxidation decreased proliferation of endothelial cells, decreased sprout elongation in the sprouting assay, and decreased sprouting from the axial vein in the zebrafish model. ATP production was not affected. Therefore, it was hypothesised that DLL4-NOTCH activation promotes and maintains the stalk cell phenotype through an increase of fatty acid oxidation, thereby promoting biomass production for endothelial cell proliferation and growth during angiogenic sprout elongation. Thirdly, a key fatty acid metabolism gene, fatty acid binding protein 4 (FABP4), was identified, that is positively regulated by NOTCH at its promoter region. FABP4 is a candidate for mediating increased fatty acid flux in endothelial cells in response to DLL4-NOTCH. This study shows that FABP4 is induced by VEGFA in a manner dependent on DLL4-NOTCH, and the insulin-responsive transcription factor FOXO1 was required for FABP4 expression in response to DLL4-NOTCH. FABP4 is pro-angiogenic and implicated in tumour angiogenesis in ovarian cancer omental metastasis. Taken together, this study shows for the first time that DLL4-NOTCH signalling increases FABP4 induction, contributing to a key pro-angiogenic pathway, and also fatty acid utilisation in endothelial cells, and thereby contributes to the formation of blood vessels.